Securing Indonesia Cyber Space: Strategies for Cyber Security in the Digital Era - Futri Bela Fransiska; Fredy BL. Tobing (Jurnal Studi Sosial dan Politik, 2023)
Abstract The development of information and communication technology is increasing, this is directly proportional to the number of users who experience a significant increase every year, this makes the world borderless and timeless in one cyberspace then the state needs to guarantee the security of information and data in cyberspace from crime. cyber. In this study using a qualitative research methodology with secondary data collection, in this study it is known that Indonesia is working to strengthen cyber security through bilateral, multilateral, and cyber diplomacy cooperation with various relevant agencies such as the Ministry of Foreign Affairs, the Ministry of Defense, or the BSSN.